If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 = 6 * 175 + b Multiply 6 * 175 29 = 1050 + b Solving 29 = 1050 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 29 + -1b = 1050 + b + -1b Combine like terms: b + -1b = 0 29 + -1b = 1050 + 0 29 + -1b = 1050 Add '-29' to each side of the equation. 29 + -29 + -1b = 1050 + -29 Combine like terms: 29 + -29 = 0 0 + -1b = 1050 + -29 -1b = 1050 + -29 Combine like terms: 1050 + -29 = 1021 -1b = 1021 Divide each side by '-1'. b = -1021 Simplifying b = -1021
| 17=6*75+b | | -16x^2+96x=0 | | t-(-16)=9 | | -8-(-10)= | | 0.7(4x+8)=1.7-(x+2) | | y+0.2=0.6y+1.8 | | 23=6*125+b | | 56=2x-9x | | 8x^2-x+6=0 | | 84=9x+7 | | ln(3x)+ln(2x)=9 | | 2(x-1)+3(2x+1)=-7 | | 84=9x+10 | | -4-(-6)= | | x-7=6x-3 | | 12x^2=28 | | 3g+3=5(3*g) | | -46k-19(k-8)-(4-2k)= | | -46k-19(l-8)-(4-2k)= | | 3.5x+6=12.5 | | x-9=-6x-3 | | -19(3p-115)-425+234p= | | 7(u-8)=(3u+4) | | 1+3x=x | | 90=10x+75 | | 696969= | | y+6(8-2y)-3(7+x)+9= | | p^2+3p-4=0 | | 53-(4x+3)=4(x+8)+x | | 10x-3=63 | | 4+4=y | | 9x+5y=45 |